Ocorrência de sementes com casca aberta na produção de sementes de arroz híbrido irrigado no estado de Roraima - Soares, Maurício Jurê (2011)
The production of hybrid rice seeds in the state of Roraima takes place in two crops per year. About 70% of which is held between the months October to March the following year, called the summer crop, and the remaining 30% occur in the winter season (April to September of that year). Yields of winter of 2009, 2010 and 2011 were limited by the occurrence of shelled seeds in open fields to produce the Hybrid rice seeds, cultivar Avaxi CL. The objective of this study was to survey the occurrence of seeds in shell open in the three growing seasons of winter and their problems in losses in seed processing and seed quality. Data were presented on the loads of trucks coming from the seed production fields. The procedures for obtaining samples and the sampling intensity were performed in accordance with Rules for Seed Analysis. The data of the percentage of open shelled seeds was systematized by the truck loads of seeds, depending on the time of seed harvest and according to the different areas used for seed production. Data were also taken for germination of seed lots produced and thousand seed weight. Yields were low harvests in 2009, 2010 and 2011, for this season, in relation to productivity typically observed in summer crops. The occurrence of seeds with open shells ranged from 15.1% to 29.9%, and this variation associated with the harvest season and growing season. Seeds with open shells can be separated in the beneficiation process, causing, however, severe yield losses in seed processing unit. Although with high levels of discarding in the processing of seeds is possible to obtain seeds with high physiological quality, and maintenance of the thousand seed weight of cv. Key words: Oryza sativa, seed quality, losses in processing.